Insights into polyethylene biodegradative fingerprint of Pseudomonas citronellolis E5 and Rhodococcus erythropolis D4 by phenotypic and genome-based comparative analyses - Zampolli, Jessica; Collina, Elena; Lasagni, Marina; Di Gennaro, Patrizia (Frontiers in Bioengineering and Biotechnology, 2024)
Polyethylene (PE) is the most produced polyolefin and consequently, it has been the most found plastic waste worldwide. PE biodegradation is under study by applying different (micro)organisms in order to get deeper into the biodegradative mechanism in the majority of microbes. This study aims to identify novel bacterial species with compelling metabolic potential and strategic genetic repertoire for PE biodegradation. Pseudomonas citronellolis E5 is newly isolated from a solid organic waste contaminated with plastic debris and Rhodococcus erythropolis D4 was selected for its promising potential in biodegrade plastic determined by its genetic repertoire. P. citronellolis E5 was selected for its ability to grow on PE as the only carbon and energy source and the meaningful laccase activity extracellular secreted was also characterized for D4 during growth on PE (E5 and D4 strains have a laccase activity of (2±1) *10 -3 U mg -1 and of (3±1) *10 -3 U mg -1 , respectively).Despite the highest level of cell number recorded at 7 days of growth on PE for both strains, the pattern of the metabolic products obtained and degraded during 60 days on PE was dissimilar in the two bacteria at different sampling times. However, they mainly produced metabolites belonging to carboxylic acids and alkanes with varying numbers of carbons in the aliphatic chains. Moreover, whole-genome sequence analysis of P. citronellolis E5 compared to R. erythropolis D4, and genetic determinant prediction (by gene annotation and multiple sequence alignment with reference gene products) have been performed providing a list of 16 and 42 gene products putatively related to different metabolic steps of PE biodegradation. Altogether, these results support peculiar insights into PE biodegradation in bacteria of Pseudomonas and Rhodococcus genus from metabolic and genetic perspectives as a base to build up novel biotechnological platforms.